2020
DOI: 10.1186/s12864-020-06819-0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of the most barotolerant Listeria monocytogenes RO15 strain compared to reference strains used to evaluate food high pressure processing

Abstract: Background: High pressure processing (HPP; i.e. 100-600 MPa pressure depending on product) is a non-thermal preservation technique adopted by the food industry to decrease significantly foodborne pathogens, including Listeria monocytogenes, from food. However, susceptibility towards pressure differs among diverse strains of L. monocytogenes and it is unclear if this is due to their intrinsic characteristics related to genomic content. Here, we tested the barotolerance of 10 different L. monocytogenes strains, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(61 citation statements)
references
References 72 publications
(95 reference statements)
3
58
0
Order By: Relevance
“…For example, it has been shown that a mutation in ctsR causes barotolerance and a ctsR deletion mutant of L. monocytogenes shows increased expression of Clp protease and PTS system genes after HPP [31]. Similarly, we previously reported that heat-shock and Clp protease family genes were upregulated after HPP [12]. In contrast, Bowman et al [32] reported downregulation of heat-shock and PTS system genes after HPP.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…For example, it has been shown that a mutation in ctsR causes barotolerance and a ctsR deletion mutant of L. monocytogenes shows increased expression of Clp protease and PTS system genes after HPP [31]. Similarly, we previously reported that heat-shock and Clp protease family genes were upregulated after HPP [12]. In contrast, Bowman et al [32] reported downregulation of heat-shock and PTS system genes after HPP.…”
Section: Introductionmentioning
confidence: 72%
“…The previous studies used relatively higher temperatures for storage after HPP (⩾ 15 °C) compared to common coldstorage applications in the food industry. We recently showed genetic differences between barotolerant and barosensitive L. monocytogenes strains, which may explain their different HPP sensitivity [12]. Hence, in the present study, we investigate the transcriptional response to HPP and the differences in gene expression pro les between barotolerant and barosensitive L. monocytogenes strains during recovery.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations